2015
DOI: 10.15177/seefor.15-13
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Use of Indigobush (Amorpha fruticosa L.) as Natural Resource of Biologically Active Compounds

Abstract: Background and Purpose: Recent research indicates that a weed like Indigobush (Amorpha fruticosa L.) gives great opportunities for its commercialization through a rich spectrum of its beneficial biological features with possible use in the forestry and biotechnology field. Therefore, in this study we wanted to explore some of potential application of Indigobush extract, as a source of biologically active compounds, for animal cell culturing as well as green corrosion inhibitors. Materials and Methods: The effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…Considering IC 50 values, according to criteria of American National Cancer Institute (NCI) for cytotoxity (IC 50 < 30 μg/mL) (Suffness and Pezzuto 1990), the investigated plants did not show significant cytotoxic effects on these cell lines. The cytotoxic effects of RpE and AfE were investigated by other author on different cell lines (Frédérich et al 2009), and our data correlate with no significant cytotoxic activity of AfE, observed in Jakovljević et al (2015). Although RpE and AfE showed no significant cytotoxic activity, they still have potential application as supplements in anti-tumor therapy.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Considering IC 50 values, according to criteria of American National Cancer Institute (NCI) for cytotoxity (IC 50 < 30 μg/mL) (Suffness and Pezzuto 1990), the investigated plants did not show significant cytotoxic effects on these cell lines. The cytotoxic effects of RpE and AfE were investigated by other author on different cell lines (Frédérich et al 2009), and our data correlate with no significant cytotoxic activity of AfE, observed in Jakovljević et al (2015). Although RpE and AfE showed no significant cytotoxic activity, they still have potential application as supplements in anti-tumor therapy.…”
Section: Discussionsupporting
confidence: 65%
“…Antispasmodic, diuretic and anticancer effect of R. pseudoacacia (due bensaldehyde isolated from flowers of this plant) were confirmed (Duke and Wain 1981). Amorpha fruticosa shows anticancer, antimicrobial and antioxidant activity (Jakovljević et al 2015).…”
Section: Introductionmentioning
confidence: 73%